Intensification of storm water treatment of wood transfering wood termination facilities - Tatyana Yu. Popova; Viktor L. Golovin; Vladislava N. Volkova (RUDN Journal of Ecology and Life Safety, 2024)
The study presents the experience of operating water treatment plants, analyzes the dangerous consequences of pre-chlorination during the discoloration of natural waters, and examines the mechanisms of action of chlorine-containing components on organic impurities contained in untreated water. The necessity of pretreatment of water before prechlorination, which ensures the mandatory destruction of organo-complex compounds, has been determined. The principles of pretreatment of natural waters in a biologically active environment are substantiated, which will eliminate the formation of toxic substances and pathogenic microorganisms.